Analisis Pendidikan Karakter Pada Mata Pelajaran IPA di Sekolah Dasar - Fina Dwi Sastafiana; Eni Setyowati (The Elementary Journal, 2023)
Character education in the learning process is a process of forming students' character in introducing ethical values. So, in the science learning process, teachers play a very important role in developing character education as the internalization of students' character through the learning process. This research was carried out using a literature review research method which provides output on existing data, as well as an explanation of a discovery so that it can be used as an example for research studies in compiling or creating a clear discussion of the content of the problem to be researched. The aim of this research is to conduct an in-depth analysis of character education in science subjects. This analysis involves an in-depth understanding of the planning stages prepared by teachers in the character education process, the application of character education to students, and the process of assessing student character education. The results of this research show that in science learning a lot is done to shape students' characters such as honesty, discipline, hard work, thoroughness, and increasing curiosity